The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1161/circimaging.114.003397
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Findings Predict In-Hospital and 1-Year Mortality in Left-Sided Native Valve Staphylococcus aureus Endocarditis

Abstract: Background Staphylococcus (S.) aureus left-sided native valve infective endocarditis (LNVIE) has higher complication and mortality rates compared with endocarditis from other pathogens. Whether echocardiographic variables can predict prognosis in S. aureus LNVIE is unknown. Methods and Results Consecutive patients with LNVIE, enrolled between January 2000 and September 2006, in the International Collaboration on Endocarditis were identified. Subjects without S. aureus IE were matched to those with S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Overall, 15 included studies were from Europe [], six from Asia [ 32 33 34 35 36 37 ], one from Africa [ 38 ], and the remainder studies were intercontinental encompassing many countries [ 39 40 41 ]. We identified 14 retrospective and 11 prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 15 included studies were from Europe [], six from Asia [ 32 33 34 35 36 37 ], one from Africa [ 38 ], and the remainder studies were intercontinental encompassing many countries [ 39 40 41 ]. We identified 14 retrospective and 11 prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Endocarditis is among the most feared complications of SAB with a reported incidence of 25–29% and a 1-year mortality rate up to 43% [ 3 , 15 , 24 ]. This complication is difficult to diagnose since the initial clinical symptoms and signs are insensitive and non-specific [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus bacteraemia (SAB) is associated with a long hospital stay, a high morbidity and high 30-day mortality numbers ranging from 10 to 30% [ 1 , 2 ]. The mortality is associated with the development of serious complications such as metastatic abscesses, vertebral osteomyelitis and acutely life-threatening complications such as endocarditis, intracardiac abscesses and valve perforation [ 3 ]. Important in the management of SAB is to correctly classify SAB as either uncomplicated or complicated and to detect the complications as quickly as possible.…”
Section: Introductionmentioning
confidence: 99%
“…They found a one-year all-cause mortality of 56.3% among all IE cases. In a study from the International Collaboration on Endocarditis-cohort, Lauridsen et al reported the all-cause one-year mortality among patients with left-sided native valve S. aureus endocarditis to 43%, which is consistent with the current non-ESKD population [35]. Hemodialysis patients were not excluded in the study by Lauridsen et al, but only accounted for 12% of their population.…”
Section: Discussionmentioning
confidence: 82%